PENINGKATAN KEMANDIRIAN SISWA KELAS XII DALAM PENETAPAN KEPUTUSAN RENCANA SETELAH TAMAT SMA (KARIR) MELALUI TEKNIK KOMBINASI LAYANAN BIMBINGAN DAN KONSELING DI SMA NEGERI 8 BATANGHARI - Iyut Mardiati (Yayasan Literasi Kita Indonesia, 2020)
This research is a research action (action Research) where students are given the form of guidance and counseling services which is a combination of group guidance services, information services and PKO services in order to increase the student self-reliance in decision making in the career assignment plan after graduating high school. Data analysis is quantitative and qualitative to describe the students ' state to analyze the effectiveness of students ' guidance and counseling services. The results of the study gained that students desperately needed information about continued education and employment after graduating high school, 84.46% of students expressed a very concur and 14.90% expressed concur. The effectiveness of group tutoring was described that effective service activities for students of 81.03% expressed very concur, 17.82% agreed and 1.15% were less agreed.
Students are also self-reliant and confident in the application of a career renceration decision after graduating high school which is 83.49% of students expressed a very concur, 16.83% expressed consent, 2.89% of students disagree, 0.98% disagree. From the results of observations to students during the Research counseling action implemented 83.65% of students ' interest in good category, 89.42% of students ' attention is good, 94.23% of student enthusiasm is good category, confident students both reach 85.58%, and the social relationship of students is also good i.e. reaching 83.65%. Action Research (Action Research) is effective and suitable to students ' needs and make students more steady in planning a career to be selected after graduating from high school that is based on the observation recap of 87.31% activity in the category good, this proves that the service is implemented according to the needs of students especially class XII students to increase self-reliance in deciding the future plan (career) after graduating.